Senten?as relativas em cartas de in?beis - Mascarenhas, Janaina de Oliveira Costa (2016)
The main goal of this work is to identify and describe relative clauses in 91 personal letters written between 1906 and 2000 by semi-illiterate Bahian inlanders, edited by Santiago (2012), who has called them unskilled hands (MARQUILHAS, 2000). From the analysis of the process of relative clauses construction by these writing-subject, it is intended to describe the relativizing strategies employed, observing either their similarity with popular variants of Brazilian Portuguese (TARALLO, 1983, 1993), or trying to understand whether these processes are similar to those in specific clauses of adults who are acquiring the written language, as relative clauses analyzed in studies of language acquisition by children (LESSA DE OLIVEIRA, 2008), or if it happens in both situations. To do so, the researchwas based on the theoretical assumptions of the Historical Linguistics (socio-historical perspective) as defined by Mattos e Silva (2008) and the Labovian Sociolinguistics theory (LABOV, 1972).